2021
DOI: 10.1021/jacs.1c07522
|View full text |Cite
|
Sign up to set email alerts
|

Cubic AgMnSbTe3 Semiconductor with a High Thermoelectric Performance

Abstract: The reaction of MnTe with AgSbTe 2 in an equimolar ratio (ATMS) provides a new semiconductor, AgMnSbTe 3 . AgMnSbTe 3 crystallizes in an average rock-salt NaCl structure with Ag, Mn, and Sb cations statistically occupying the Na sites. AgMnSbTe 3 is a p-type semiconductor with a narrow optical band gap of ∼0.36 eV. A pair distribution function analysis indicates that local distortions are associated with the location of the Ag atoms in the lattice. Density functional theory calculations suggest a specific elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 68 publications
1
71
1
Order By: Relevance
“…This local structural distortion can give rise to additional phonon− phonon scattering, which can reduce the κ lat of this material. 42,43 Temperature dependent (100−400 K) total X-PDF data (r = 2.0−20 Å) fitted using rock-salt model indicated that the overall structure becomes more ordered with the increase in temperature as evident from the R w data (Figure 4a). The R w value decreases from 0.101 at 100 K to 0.087 at 400 K. The lattice parameter and the isotropic atomic displacement parameters (U iso ) obtained through cubic fitting are found to increase with temperature (Figure S2, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This local structural distortion can give rise to additional phonon− phonon scattering, which can reduce the κ lat of this material. 42,43 Temperature dependent (100−400 K) total X-PDF data (r = 2.0−20 Å) fitted using rock-salt model indicated that the overall structure becomes more ordered with the increase in temperature as evident from the R w data (Figure 4a). The R w value decreases from 0.101 at 100 K to 0.087 at 400 K. The lattice parameter and the isotropic atomic displacement parameters (U iso ) obtained through cubic fitting are found to increase with temperature (Figure S2, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Such asymmetry has been attributed to multiple unresolved long and short bond lengths present between the atoms. This local structural distortion can give rise to additional phonon–phonon scattering, which can reduce the κ lat of this material. , …”
Section: Resultsmentioning
confidence: 99%
“…However, the effectiveness of these strategies is limited according to the defect type and the wavelengths of phonons [18,[38][39][40][41][42]. Alternatively, other strategies, such as band structure modulation, entropy engineering, and preferential scattering of minority carriers, can be explored, which aim to improve other components of thermal conductivity as well [43][44][45][46][47][48][49][50][51][52][53]. More recently, a fresh perspective on engineering next-generation high-performance thermoelectrics has been reported, which includes low doping, in contrast to the "golden range of carrier concentration" [54,55].…”
Section: Thermoelectric Devicesmentioning
confidence: 99%
“…The classic theory of phonon glass electron crystal (PGEC) provides a route to design a high-ZT thermoelectric material with higher electrical performance and low thermal conductivity. Therefore, numerous separate approaches have been devoted to optimizing the electrical and thermal properties, thus increasing the ZT value, and the electrical performance can be optimized via point defects (PDs) [13,14], band engineering [15,16], and high-entropy engineering [17,18]. In contrast, the microstructure engineering induced by nanocompositing [19,20], dislocations [21,22], and hierarchical architecture [23,24], has been employed and proven to be effective in reducing the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%